Hubungan Program Sanitasi Total Berbasis Masyarakat (STBM) Dengan Kejadian Diare Pada Masyatakat Yang Tidak Memiliki Jamban Di Wilayah Kerja Puskesmas Berohol Kota Tebing Tinggi Tahun 2019 - Maghdalena Br Barus; Fithri Handayani Lubis; Taruli Nadeak (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2020)
The number of Diarrhea KLB Cases in 2010 was 2,580 with77 deaths (CFR2.98%). This result was different from 2009 where there were 3,307 cases of diarrhea KLB, 21 cases of deaths (CFR0.69%). And the latrines ownership is one of the causes. Good total sanitation decreases 94% of diarrhea. The purpose of this study is to determine the relationship between total community-based sanitation programs and the incidence of diarrhea incommunities who do not own latrines. This type of research uses Cross Sectional research. The population of this study is all communities that reside in the working area of​Puskesmas Berohol of Tebing Tinggi City. The sample is 60 respondents using the Simple Random Sampling technique. Instrument research questionnaire and observation sheet. The results of this study state that there is a relationship between the total community-based sanitation program and the incidence of diarrhea in people who do not have latrines, wherethep-valueis 0.002 < 0.05. The conclusion is based on there search about there lationship of Community Based Total Sanitation Program (STBM) with Diarrhea Incidence in Communities that Do Not Have Latrines in the Work Area of​​ the Alcoholic Health Center of Tebing Tinggi City in 2019. The results obtained are that there is a relationship between the total community-based sanitation program (STBM) and the incidence of diarrhea. Suggestions for the community to improve the individual of total sanitation.